In vitro activity of Piper sarmentosum ethanol leaf extract against Toxoplasma gondii tachyzoites - Devanthran, K; Unyah, Z; Majid, RA; Abdullah, WO (Pharmacotherapy Group, 2024)
Purpose: To evaluate the activity of the ethanol leaf extract of Piper sarmentosum against toxoplasmosis. Methods: An in vitro anti-Toxoplasma study was conducted using Vero cells as a host for T. gondii. Clindamycin used as the reference drug. Light microscopy technique was used to study the in situ antiparasitic activity of T. gondii. Non-toxic concentrations of the ethanol extract for Vero cells were determined by methyl thiazolyl tetrazolium (MTT) cell proliferation. The presence of Toxoplasma gondii was observed by Giemsa staining. Results: The results showed that significant (p < 0.05) anti-toxoplasma activity of the ethanol extract, though lower than that of clindamycin (control drug), was achieved, with half-maximal inhibitory concentration (IC50) of 12.4 and 7.2 mu g/mL for the extract and reference drug, respectively. After 24 hours of exposure to the extract, the inoculated Vero cells showed lower parasitemia and no remarkable morphological changes. Conclusion: The findings demonstrate that the ethanol extract of P. sarmentosum leaves are active against toxoplasmosis in vitro. However, further studies are required to determine the therapeutic significance of these findings in vivo.